2019
DOI: 10.1105/tpc.18.00960
|View full text |Cite
|
Sign up to set email alerts
|

The MCTP-SNARE Complex Regulates Florigen Transport in Arabidopsis

Abstract: Multiple flowering pathways in Arabidopsis (Arabidopsis thaliana) converge on the transcriptional regulation of FLOWERING LOCUS T (FT), encoding a mobile floral stimulus that moves from leaves to the shoot apex. Despite our progress in understanding FT movement, the mechanisms underlying its transport along the endoplasmic reticulum-plasmalemma pathway in phloem companion cells remain largely unclear. Here, we show that the plasma membrane-resident syntaxin-like glutamine-soluble N-ethylmaleimide-sensitive fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 57 publications
2
61
0
Order By: Relevance
“…FT is highly conserved across angiosperm species and its gene expression in Arabidopsis is mainly activated by CONSTANS (CO), but suppressed by other repressors, such as MYC3 in the GA signaling pathway, in leaves (Samach et al ; Suárez‐López et al ; An et al ; Valverde et al ; Bao et al ). Its protein is mediated by multiple regulators to move via the phloem into the shoot apex (Liu et al , ; Zhu et al ; Liu et al ), where it promotes the expression of another floral integrator SOC1 and the floral meristem identity gene AP1 (Wigge et al ; Notaguchi et al ). SOC1 and another floral integrator LFY mainly function in the shoot apex, and their messenger RNA (mRNA) expression is tightly regulated by endogenous GA levels and some other flowering time genes acting in the shoot apex, such as AGL24 (Yu et al ; Moon et al ; Eriksson et al ; Liu et al ; Hou et al ).…”
Section: Introductionmentioning
confidence: 99%
“…FT is highly conserved across angiosperm species and its gene expression in Arabidopsis is mainly activated by CONSTANS (CO), but suppressed by other repressors, such as MYC3 in the GA signaling pathway, in leaves (Samach et al ; Suárez‐López et al ; An et al ; Valverde et al ; Bao et al ). Its protein is mediated by multiple regulators to move via the phloem into the shoot apex (Liu et al , ; Zhu et al ; Liu et al ), where it promotes the expression of another floral integrator SOC1 and the floral meristem identity gene AP1 (Wigge et al ; Notaguchi et al ). SOC1 and another floral integrator LFY mainly function in the shoot apex, and their messenger RNA (mRNA) expression is tightly regulated by endogenous GA levels and some other flowering time genes acting in the shoot apex, such as AGL24 (Yu et al ; Moon et al ; Eriksson et al ; Liu et al ; Hou et al ).…”
Section: Introductionmentioning
confidence: 99%
“…FT protein has been identified as part of florigen that moves from leaves to the shoot apex through the phloem system and this long-distance trafficking is mediated by several regulators (Liu et al 2012(Liu et al , 2013(Liu et al , 2019Zhu et al 2016). The members of the family of multiple C2 domain and transmembrane region proteins (MCTPs) and soluble N-ethylmaleimidesensitive factor protein attachment protein receptor (SNARE) proteins are evolutionarily conserved proteins and mediate the trafficking of FT and several other developmental regulators (Grefen and Blatt 2008;Liu et al 2018aLiu et al , 2018bSong et al 2018Song et al , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, this analysis revealed a specific interaction with QKY rather than FT-INTERACTING PROTEIN1 (FTIP1), an MCTP previously implicated in FT movement through the endoplasmic reticulum (Liu et al, 2012). Phenotypic analysis of qky mutants and knockdown lines demonstrated delayed flowering time in long days relative to wildtype plants (Liu et al, 2019). Expression analysis using promoter-reporter fusions revealed that QKY expression is restricted to phloem CCs, and subcellular localization studies determined that QKY-GFP is located in endosomal vesicles and colocalizes with RFP-SYP121 at the plasma membrane.…”
mentioning
confidence: 88%
“…The underlying molecular mechanisms controlling FT movement from phloem companion cells (CCs) to sieve elements (SEs) for access to the phloem translocation stream are not well understood. To address this issue, Liu et al (2019) genetically interrogated membrane-resident soluble N-ethylmaleimide-sensitive factor protein attachment protein receptor (SNARE) proteins controlling endosomal vesicular trafficking for potential roles in regulating the CC-to-SE movement of FT during photoperiod flowering in Arabidopsis. The authors identified a late-flowering phenotype exclusively in syntaxin of plants 121 (syp121-4) mutants under long-day conditions that was recapitulated by artificial microRNA-mediated SYP121 knockdowns in wild-type plants and complemented by transforming a genomic gSYP121 fragment back into syp121-4.…”
mentioning
confidence: 99%
See 1 more Smart Citation